Reductive stress impairs myoblasts mitochondrial function and triggers mitochondrial hormesis - Singh, François; Charles, Anne-Laure; Schlagowski, Anna-Isabel; Bouitbir, Jamal; Bonifacio, Annalisa; Piquard, François; Krähenbühl, Stephan; Geny, Bernard; Zoll, Joffrey (Biochimica et biophysica acta, 2015)
Even though oxidative stress damage from excessive production of ROS is a well known phenomenon, the impact of reductive stress remains poorly understood. This study tested the hypothesis that cellular reductive stress could lead to mitochondrial malfunction, triggering a mitochondrial hormesis (mitohormesis) phenomenon able to protect mitochondria from the deleterious effects of statins. We performed several in vitro experiments on L6 myoblasts and studied the effects of N-acetylcysteine (NAC) at different exposure times. Direct NAC exposure (1mM) led to reductive stress, impairing mitochondrial function by decreasing maximal mitochondrial respiration and increasing H2O2 production. After 24h of incubation, the reactive oxygen species (ROS) production was increased. The resulting mitochondrial oxidation activated mitochondrial biogenesis pathways at the mRNA level. After one week of exposure, mitochondria were well-adapted as shown by the decrease of cellular ROS, the increase of mitochondrial content, as well as of the antioxidant capacities. Atorvastatin (ATO) exposure (100μM) for 24h increased ROS levels, reduced the percentage of live cells, and increased the total percentage of apoptotic cells. NAC exposure during 3days failed to protect cells from the deleterious effects of statins. On the other hand, NAC pretreatment during one week triggered mitochondrial hormesis and reduced the deleterious effect of statins. These results contribute to a better understanding of the redox-dependant pathways linked to mitochondria, showing that reductive stress could trigger mitochondrial hormesis phenomenon. •NAC reductive stress impairs myoblasts mitochondrial respiratory chain function.•Mitochondrial malfunction leads to mitochondrial ROS production.•Mitochondrial oxidation triggers the mitochondrial hormesis phenomenon.•Mitochondrial hormesis protects myoblasts from the toxic effects of statins.